Integrated Energy Devices: 3D Heteroatom‐Doped Carbon Nanomaterials as Multifunctional Metal‐Free Catalysts for Integrated Energy Devices (Adv. Mater. 13/2019). Issue 13 (25th March 2019) - Paul, Rajib; Du, Feng; Dai, Liming; Ding, Yong; Wang, Zhong Lin; Wei, Fei; Roy, Ajit
Abstract : Metal‐free carbon‐based three‐dimensional structures are very promising for efficient electrocatalysis towards multifunctional energy storage and conversion. Heteroatom doped isotropic and hierarchical carbon electrode fabrication through chemical vapor deposition and 3D‐printing for next‐generation integrated energy applications are summarized by Liming Dai, Zhong Lin Wang, Ajit Roy, and co‐workers in article number1805598 .